Gamma Irradiation of Plukenetia volubilis L. Seeds Promotes Several Changes during Its Germination and Vegetative Growth - Mike Anderson Corazon-Guivin; Sofia Rengifo-Del Aguila; Angel David Hernández-Amasifuen; Víctor Manuel Arévalo-Rojas; Ronny Anthony Acosta-Córdova; Agustín Cerna-Mendoza; Thiago de Araújo Mastrangelo; Jorge Damian Valverde-Iparraguirre; Juan Carlos Guerrero-Abad (Advances in Agriculture)
Plukenetia volubilis (“sacha inchi”) is a perennial plant that produces edible seeds with a remarkable lipid composition that is highly concentrated in polyunsaturated essential fatty acids. Inca nut seeds have potential use for lowering malnutrition, enhancing sustainable food production systems, reforestation, and the pharmaceutical industry. The establishment of genetic variability, through spontaneous mutations or induced mutations, can bring desirable and undesirable agronomic traits. Our research focused on studying the impact of gamma radiation on P. volubilis seeds during their germination and vegetative growth. For this purpose, we exposed seeds to different doses of gamma irradiation (0, 500, 550, 600, 650, 700, 750, 800, and 900 Gy) and planted them under in vitro and greenhouse conditions following a completely random design. Our findings showed that gamma radiation treatments did not affect the germination of P. volubilis seeds but affected its root tip growth. An analysis on morphological and physiological parameters revealed a reduction in seedling size and weight when the irradiation doses were increased. Also, the pattern of plant organ development changed as its gamma irradiation was increased. Finally, our analysis found that median lethal dose (LD50) for P. volubilis L. seeds is 618.78 Gy. Our findings can be used as an important reference for plant breeding in this species.